Importance of including entrepreneurship in the municipal development plans (2019)
The socio-economic development for the State is an aspect of vital importance in the projections and supports assigned to a population in a specific territory. For this reason, in Colombia, a diversity of actions, plans and programs are established that aim to promote this aspect, focused on a local level. The generation of socio-economic development is aimed at improving the quality of life of its population, posing great challenges for leaders, who are responsible for guiding and structuring their development plans into management tools planned during their period of government to promote the efficient fulfillment of goals and proposals raised to the community of a territory. Entrepreneurship is positioned as one of the pillars to overcome poverty and generate economic alternatives for integral development in a population, through support for initiatives and business units, where the state includes goals in its development plans and allocates the necessary resources. for that end